Variations and continuities: the use of animal resources during the 20th century among indigenous settlements of central-western Santa Cruz - Agnolin, Agustín M. (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
This article focuses on the resource exploitation strategies used by indigenous family-units that inhabited the Strobel Lake plateau (Santa Cruz province) during the 20th century. The groups that settled in this region avoided being incorporated into the indigenous reservations created by the national state. The family-units adopted varied economic strategies in order to occupy these spaces. These strategies were marked by accommodation and readjustment to the advancing pastoralist economy and the loss of lands. We conclude that the strategies adopted were characterized by diversity and flexibility; combining traditional practices with others linked to the new role that these groups acquired within the new economy. Notwithstanding, the creation of new laws and the progressive encirclement of these local groups led them to abandon their settlements on the plateau.